(untitled) (Research, Society and Development, 2021)
The phenolic compounds from olive tree products (Olea europaea L.) have antitumor potential through their effects in the prevention of tumor genesis and tumor suppression in different cancer models. This article aims to carry out a literature review, through an integrative review, on the antitumor potential of phenolic compounds in olive tree products. This is an integrative literature review, qualitative and exploratory, based on pre-clinical, in vitro and in vivo studies, published in journals indexed in databases that address the subject. The search, without date restriction, was performed in the Web of Science, PUBMED and Scopus databases. Evidence suggests that phenolic compounds from olive products (oleuropein, hydroxytyrosol, tyrosol and oleocanthal) may exert tumor genesis inhibiting effects, such as repair and protection against damage from oxidative stress and chronic inflammation, and thus could help in reducing the risk of cancer, delaying the development, progression or recurrence of various types of tumors. The analysis of the studies demonstrated antitumor potential of the olive tree phenolic compounds as they present anticancer activity through the reduction of cell growth and viability, inhibition of cell proliferation, migration and invasion, modulation in cell cycle phases and induction of apoptosis in different tumor models.